Method of value chain mapping with international input-output data: Application to the agricultural value chain in three Greater Mekong Subregion countries - Ikuo Kuroiwa (Journal of Economic Structures, 2021)
Extending the technique of unit structure analysis, which was originally developed by Ozaki (J Econ 73(5):720-748, 1980), this study introduces a method of value chain mapping that uses international input-output data and reveals both the upstream and downstream transactions of goods and services,~as well as primary input (value added) and final output (final demand) transactions,~which~emerge along the entire value chain. This method is then applied to the agricultural value chain of three Greater Mekong Subregion countries: Thailand, Vietnam, and Cambodia. The results show that the agricultural value chain has been increasingly internationalized, although there is still room to benefit from participating in global value chains, especially in a country such as Cambodia. Although there are some constraints regarding the methodology and data, the method proves useful in tracing the entire value chain.
Keywords: 330; Agricultural value chains; Trade in value added; Value chain mapping